2017
DOI: 10.1016/j.bbamcr.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Rab7a regulates cell migration through Rac1 and vimentin

Abstract: Rab7a, a small GTPase of the Rab family, is localized to late endosomes and controls late endocytic trafficking. The discovery of several Rab7a interacting proteins revealed that Rab7a function is closely connected to cytoskeletal elements. Indeed, Rab7a recruits on vesicles RILP and FYCO that are responsible for the movement of Rab7a-positive vesicles and/or organelles on microtubule tracks, but also directly interacts with Rac1, a fundamental regulator of actin cytoskeleton, and with peripherin and vimentin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 76 publications
5
59
0
Order By: Relevance
“…11,33 Furthermore, we recently demonstrated that Rab7a controls cell migration by influencing adhesion and spreading on fibronectin. 14 Here, we demonstrated that also RILP plays a role in cell adhesion and spreading to fibronectin. Indeed, RILP overexpression decreased the adhesion and spreading on fibronectin compared to control cells (Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…11,33 Furthermore, we recently demonstrated that Rab7a controls cell migration by influencing adhesion and spreading on fibronectin. 14 Here, we demonstrated that also RILP plays a role in cell adhesion and spreading to fibronectin. Indeed, RILP overexpression decreased the adhesion and spreading on fibronectin compared to control cells (Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 64%
“…This is interesting considering that alterations of migration are found in cancer cells and that also Rab7a regulates migration. 14 In particular, Rab7a seems to favor or suppress cancer progression depending on the cell type or district of tumor. 17,29,30 Indeed, Rab7a oncosuppressing role has been demonstrated in prostate cancer cells where its depletion affected lysosome localization, increasing tumor cell invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HGF stimulation also induced c-Met-dependent Rac1 activation in perinuclear, Rab7-positive endosomes by engaging the specific effectors PI3K and the GEF Vav2 to activate cell migration and invasion [125]. Additionally, Rab7 was shown to directly interact with Rac1 on endosomes, thereby enabling Rac1 activation and promoting Rac1 delivery to the PM to stimulate cell migration [129]. On the other side, RhoB was shown to act as a negative regulator of Rac1 activity.…”
Section: Rho Gtpases Acting Along the Endocytic Pathwaymentioning
confidence: 99%
“…Progida presented the results of the motility screens and control experiments for reduced cell proliferation. Their recent results demonstrating that one of the candidates, RAB7a, does regulate cell migration has just been published [77]. Like RAB7b, RAB7a also regulates the actin cytoskeleton, but through interactions with RAC1 and vimentin.…”
Section: Unconventional Role Of Proteins Normally Functioning In Cmentioning
confidence: 99%